THE ONLINE-BASED ECONOMICAL DISPUTE RESOLUTION FOR 4.0 INDUSTRY IN THE NEW NORMAL ERA - Supriyadi, Aditya Prastian; Amnesti, Sheila Kusuma Wardani; Zulaicha, Siti (Fakultas Syariah, 2021)
The New Normal era during the covid-19 pandemic resulted in industry 4.0 business players having difficulty in dealing with dispute resolution due to financial problems and policy restrictions. The reformation of online dispute resolution media is needed due to the difficulty of mobility and the high cost cutting. Before the implementation, it is necessary to have concrete formula of an online dispute resolution concept because the legal basis in Indonesia is not yet qualified. This study aims to conceptualize the legal basis for online dispute resolution in the business world, which is currently not accommodated by the Indonesian laws. It also examines the development of an online dispute resolution model as a technical regulation applied to the industrial sector 4.0. This study uses legal normative research. The study approach uses an online dispute resolution conceptual system and alternative dispute resolution legislation. The results show that online dispute resolution is a new form of quick, inexpensive justice principle that can reform business law in the technology era. Several dispute resolution models can be developed online and used for implementing regulations, especially for dispute resolution media in the industrial sector 4.0.Era New Normal di masa pandemi covid-19 mengakibatkan para pelaku usaha industri 4.0 mengalami kesulitan dalam menangani penyelesaian sengketa karena masalah keuangan dan pembatasan kebijakan. Reformasi media penyelesaian sengketa secara online perlu dilakukan untuk mengatasi kendala sulitnya mobilitas dan pemotongan biaya tinggi. Sebelum dilaksanakan, terlebih dahulu perlu ada rumusan konkrit konsep penyelesaian sengketa secara online karena landasan hukum di Indonesia belum memenuhi syarat. Tujuan dari penelitian ini adalah untuk mengkonseptualisasikan dasar hukum penyelesaian sengketa online di dunia bisnis yang saat ini tidak diakomodir oleh undang-undang Indonesia. Selain itu juga mengkaji pengembangan model penyelesaian sengketa online sebagai regulasi teknis yang dapat diterapkan pada sektor industri 4.0. Studi ini menggunakan penelitian hukum normatif. Pendekatan yang digunakan ialah sistem konseptual penyelesaian sengeketa online dan perundang-undangan alternatif penyelesaian sengketa. Hasil studi menunjukkan bahwa penyelesaian sengketa online adalah bentuk baru dari asas keadilan yang cepat dan murah yang bisa mereformasi hukum bisnis di era teknologi. Beberapa model penyelesaian sengketa dapat dikembangkan secara online dan dapat digunakan sebagai dasar implementasi aturan, khususnya untuk media penyelesaian sengketa di sektor industri 4.0.